Anatomy of the clavicle and its medullary canal - a computer tomography study - King, Paul Reginald; Ikram, Ajmal; Lamberts, Robert Patrick (Stellenbosch Univeristy, 2015)
Thesis (MMed)--Stellenbosch University, 2014